A retrospective analysis of cisplatin/carboplatin plus paclitaxel in advanced or recurrent cervical cancer. (3rd April 2019) - Song, Dan; Kong, Weimin; Zhang, Tongqing; Han, Chao; Liu, Tingting; Jiao, Simeng; Chen, Jiao
Abstract: To compare the efficacy and safety of paclitaxel plus carboplatin (TC) and paclitaxel plus cisplatin (TP) in the treatment of advanced or recurrent cervical cancer, this retrospective study included 116 advanced or recurrent cervical cancer cases treated at Beijing Obstetrics and Gynecology Hospital between June 2002 and June 2014. Of these cases, 52 were treated with TC (TC group) and 64 were treated with TP (TP group). We found that the overall survival and response and disease-control rates were not significantly different between the two groups. The TC group had a markedly lower incidence of Grade III–IV gastrointestinal toxicity reactions and a shorter hospitalisation stay than the TP group. The incidences of Grade III–IV bone marrow suppression and renal toxicity were not significantly different between the TP and TC groups. These findings suggest that TC may be a safe and effective alternative to TP for the treatment of advanced or recurrent cervical cancer. Impact Statement: What is already known on this subject: Paclitaxel plus cisplatin (TP) is regarded as the standard regimen for cervical cancer, nevertheless, cisplatin is always associated with nephrotoxicity and requires hydration therapy. Carboplatin is a platinum analogue with milder nephrotoxicity than cisplatin. It is reported that carboplatin may be a viable and less toxic alternative to cisplatin in the management of advanced or recurrent cervical cancer, but another study shows that the therapeutic efficacy of paclitaxel plus carboplatin (TC) is non-inferior to that of TP. What the results of this study add: This study compared the efficacy and safety of TC and TP, and found that the TC and TP groups had similar overall response and disease-control rates and survival, but the TC group was better tolerated with a markedly lower incidence of Grades III–IV gastrointestinal toxicity reactions and had a shorter hospitalisation stay than the TP group. What the implications are of these findings for clinical practice and/or further research: TC may be a safe and effective alternative to TP for the treatment of advanced or recurrent cervical cancer in clinical practice.